Relations between generational cohorts and generations X and Y: multicultural study on Coca-Cola soft drinks - Monteiro, Thel Augusto; Giuliani, Antonio Carlos; Arroyo, Judith Cavazos; Belli, Hygino Canhadas; Oliveira, Erick Dawson de (Revista de Administração da UFSM, 2020)
The purpose of this study was to present an analysis of consumer attitudes towards the brand and its purchase intentions, as well as to explore the relationships between brand image, brand tradition, company image and beliefs regarding the brand’s role in society. As a research of a descriptive nature, it was decided to approach the research problem quantitatively through the application of a survey. The questionnaires were applied to university students from private institutions of the Business Administration course in Brazil, Spain, Mexico and Paraguay in the period of May and June 2016. The marketing scale presented by Vieira (2011) was used and validated by Pereira, Almeida and Laux (2006). Data processing for presentation and analysis was performed using the Statistical Package for Social Science (SPSS) software. The results demonstrated relevant information about consumers' attitudes towards the brand and their purchase intentions. It became evident that companies can develop marketing strategies at different levels of intensity for each of the categories analyzed and, from them, establish marketing strategies with greater criteria and objectivity in their strategies of positioning.